Bortezomib use and outcomes for the treatment of multiple myeloma. Issue 9 (14th September 2020) - Loke, Crystal; Mollee, Peter; McPherson, Ian; Walpole, Euan; Yue, Mimi; Mutsando, Howard; Wong, Phillip; Weston, Helen; Tomlinson, Ross; Hollingworth, Samantha
Abstract: Background: The public subsidy in Australia of bortezomib (Velcade) for untreated non‐transplant multiple myeloma patients was based on the VISTA trial. Aims: To ascertain the health outcomes of bortezomib in 'real world' transplant‐ineligible elderly patients, compared to trial data. Methods: Patient and treatment data were extracted from an oncology information system, laboratory information system and medical chart audits for three Queensland public hospitals. Results: We identified 74 patients; the median age was 75 years. Our cohort comprised 47% patients who were International Staging System stage III, 45% at stage II and 8% at stage I. Patients who had comorbidities, such as cardiac disease (41%), pulmonary disease (14%), diabetes (22%), peripheral neuropathy (14%) and other comorbidities (41%) at baseline were included. The common regimens prescribed were VMP, CVD and VD, and most patients ( n = 73) received bortezomib on a once‐weekly or twice‐a‐week basis. The overall response rate was 81%. Half (53%) of the patients did not complete their planned therapy due to toxicity (30%), suboptimal response or disease progression (15%), or death on treatment (8%). Overall survival was 40.7 months and progression free survival was 17.7 months. Conclusions: Our patients were older, had worse disease characteristics and more comorbidities than patients in the VISTA trial. While response rates were similar, survival outcomes appeared worse. Bortezomib‐based treatment in the real world setting still carries a high risk of toxicity in the elderly population.